Dakwah Lingkungan Perspektif Al-Qur’an - Asep Muhyiddin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
Da’wah have tight catch with various etnics, one of them called the environment problem. This entity can be parameter if da’wah activity can give contribution to solute environmental problems. These problems can examine the exsistence of da’wah truth. Al-Qur’an as the holybook of da’wah have view that the nature is not enemy that has to subjected and submitted, but integrated with human religious world. Al- Qur’ an give moral command that related by this assignment of da’wah practicioner. One-in order to man be active practicioner in managing the environment. Two-in order to man not doing damage to environment. Three- in order to man be friendly to environment.